The People's Health (Newcastle-on-Tyne : North-East District Committee, Communist Party, 1943)
1943-10 1943 1940s 36 pages Q.— Why is it that more attention is paid by the medical profession to the curative side of their work than to the preventive side? A.— I am afraid that the majority of medical men through necessity have got to deal with the curative side. I believe however the time of preventive medicine is coming. This is something which a National Health Service would make possible and one of the first questions to be tackled in this connection would be medical research. Q.— How would the Committes [Committees] or Boards responsible for the administration of a National Health Service be elected? A.— I think elections would need to be carried out in the way we are used to at the moment, that is, in the same way as we elect our representatives to local councils. Q.— What would be the position of Local Authorities under a Health Service? Doctors have something like a fear of local authorities. A.— I can sympathise to a certain extent with the doctors but as I have pointed out control would mainly rest with the Central Board of Health. There would be a national policy which the local committees would have to implement. They would not make legislation they would merely administer it. The personnel of the Local Committees would be a matter for the electors and my only hope is that they would choose wisely. Q.— Are ambulances not permitted to carry children under 1 year of age? A.— I cannot answer such a question because I do not know all local circumstances. All I know is that we have not got a National Ambulance Service and we run the risk of losing lives because of the clash of local interests and because in some cases the ambulances are run by private people. A National Ambulance Service would make an ambulance available whenever and wherever needed. Q.— What would be the position of the general practitioner under a National Health Service? A.— It is a big question but I do think he would be relieved of the scramble to live which he has got today. He would have an assured income under a National Health Service and would have through his organisations, some say in the administration of the service. He would be under the direction of the State and Local Authorities, but on the whole his position would be improved. 27 15X/2/103/295